2018
DOI: 10.1101/282210
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

WDR45 contributes to neurodegeneration through regulation of ER homeostasis and neuronal death

Abstract: Mutations in the autophagy gene WDR45 cause -propeller protein-associated neurodegeneration (BPAN); however the molecular and cellular mechanism of the disease process is largely unknown. Here we generated constitutive Wdr45 knockout (KO) mice that displayed cognitive impairments, abnormal synaptic transmission and lesions in hippocampus and basal ganglia. Immunohistochemistry analysis shows loss of neurons in prefrontal cortex and basal ganglion in aged mice, and increased apoptosis in these regions, recapit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 35 publications
4
24
0
Order By: Relevance
“…Accumulation of the ER with associated neurodegeneration has been observed in CRISPR KO mice constitutively lacking the autophagy regulatory factor WDR45 (Wan et al, 2020). Our findings are consistent with this and further suggest that ER-phagy is a major autophagic process in neurons in the absence of proteotoxic challenges at steady-state.…”
Section: Elevated Calcium Release From Er Stores Via Ryanodine Receptsupporting
confidence: 90%
“…Accumulation of the ER with associated neurodegeneration has been observed in CRISPR KO mice constitutively lacking the autophagy regulatory factor WDR45 (Wan et al, 2020). Our findings are consistent with this and further suggest that ER-phagy is a major autophagic process in neurons in the absence of proteotoxic challenges at steady-state.…”
Section: Elevated Calcium Release From Er Stores Via Ryanodine Receptsupporting
confidence: 90%
“…Previous studies demonstrated that restoring ER function is one of the available strategies for acute CNS injury, as it helps neuron against ER stress induced apoptosis [24,25]. In the present study, we also identified that upregulation of sestrin2 by AAV provides beneficial effects on reducing ER stress and apoptosis.…”
Section: Discussionsupporting
confidence: 74%
“…Though unfolded protein response (UPR) provides effect on attenuating misfolded proteins, durative ER stress without treatment ultimately exceeds the compensation and turns UPR into pro-death [22,23]. Accordingly, maintaining ER homeostasis is available for neuron regeneration and function [24,25]. In particular, a study reported by park et al [26] showed that ER stress suppressed by sestrin2 is important for hepatic rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the WDR45 protein, by binding to phosphatidylinositol-3-phosphate (PtdIns3P), regulates autophagosome formation [ 149 , 150 , 151 ]. In this way, defective autophagic flux associated with WDR45 mutations have been described in different cellular and animal studies [ 147 , 152 , 153 , 154 , 155 ]. KO mice for Wdr45 show an impaired autophagic flux with accumulation of SQSTM1- and ubiquitin-positive aggregates in neurons and swollen axons.…”
Section: Autophagosome/lysosome Regulationmentioning
confidence: 99%
“…In BPAN patients’ fibroblasts, a positive regulation of the iron transporter IRE/DMT1 (iron responsive element–divalent metal transporter 1) and a negative regulation of the transferrin receptor have been found, like in other NBIA disorders [ 153 ]. In addition, an increase in intracellular Fe 2+ after starvation have been observed, which may explain the accumulation of iron in the basal ganglia due to defects in autophagy and recycling, and alterations in lysosomal degradation [ 153 ]. IPSC-derived midbrain neurons together with fibroblasts from a BPAN woman showed augmented levels of intracellular iron and reduced levels of L-ferritin, H-ferritin and mitochondrial ferritin.…”
Section: Autophagosome/lysosome Regulationmentioning
confidence: 99%